Removal of pyrene from aqueous solutions by adsorption onto Brazilian peat samples - Francine Girardello; Suzimara Rovani; Marcelo Giovanela; Andreia Neves Fernandes (Adsorption Science & Technology)
Pyrene is a polycyclic aromatic hydrocarbon, classified as a priority pollutant. Aiming to minimize the presence of this polycyclic aromatic hydrocarbon in aquatic ecosystems, it is important to develop and consider new alternatives that enable its partial or total removal by different mechanisms and/or processes. In this sense, several techniques have been used for this purpose. Among them, adsorption techniques employing natural adsorbents as peat represent an attractive alternative due to its low cost and high removal efficiency. In the present study, two samples (decomposed peat – DP, and fibrous peat – FP) were used to remove pyrene at concentrations of 1.0, 2.0, 3.0, 4.0, and 5.0 µg L −1 for up to 72 h. The removal percentages with DP were between 75.5 and 91.0%, while for FP these values were in the range of 77.7 to 92.1%. The experimental data showed that the adsorption kinetics were better described using a pseudo-second-order model. Regarding the adsorption equilibrium, the experimental data were adequately fitted by the Freundlich equation for both peat samples. Finally, the adsorption capacity depended on thermodynamic parameters, indicating that the adsorption process was spontaneous and occurred by physisorption.